A review of diatom δ18O in palaeoceanography - Swann, George E.A.; Leng, Melanie J. (Elsevier, 2009)
Measurements of diatom oxygen isotopes (δ18Odiatom) hold the potential to provide an important additional source of palaeoceanographic information in regions depleted in carbonates. However, despite analyses of δ18Odiatom being carried out since the 1970s and the increasingly widespread use of δ18Odiatom in palaeolimnology since the 1990s, to date only a handful of studies have applied δ18Odiatom in marine reconstructions. Here the historical development and current state of affairs concerning the usage of δ18Odiatom in palaeoceanography is reviewed. This includes a summary of: